Simulation of pathological manifestations in diaphragm wall through ultrasonic wave propagation - Silva, Rodrigo Rogerio Cerqueira da Silva; Bertoldo Pedroso, Cinthya (Revista ALCONPAT, 2022)
This research aimed to simulate pathological manifestations in diaphragm wall using concrete produced with different additions of synthetic polymer, in order to obtain models of strength and stiffness prediction through ultrasound wave propagation. Compression tests were performed to determine strength and stiffness, as well as ultrasound tests by direct and indirect method on concrete produced with different concentrations of synthetic polymer. The results suggested a decrease in the mechanical and acoustic properties of concrete with the increase in the concentration of synthetic polymer. The models generated by the ultrasonic test were statistically significant, at 95% confidence level, and the correlations established in concrete can be applied in the detection of pathological manifestations in loco.